Long‐term sustained lesion clearance from Lmax with imiquimod 3.75%, a new field‐directed treatment for actinic keratosis. (29th August 2014) - Gupta, G.; Stockfleth, E.; Peris, K.; Aractingi, S.; Alomar, A.; Dakovic, R.; Dirschka, T.
Abstract Background In patients with actinic keratosis (AK), subclinical and clinical lesions coexist across large areas of sun‐exposed skin. The long‐term efficacy of AK treatments depends on their ability to eradicate both types of lesions across the entire field. Objective To assess the long‐term efficacy of imiquimod 3.75% using the reduction in lesions from Lmax (maximum lesion count during treatment), which assesses the ability to clear subclinical and clinical lesions. Methods Patients with 5–20 AK lesions on the full face or balding scalp from two 14‐week, randomized, vehicle‐controlled, double‐blind studies of imiquimod 3.75% (daily for two 2‐week treatment cycles separated by a 2‐week treatment‐free period) were eligible to enter a 12‐month follow‐up study if they had no AK lesions at Week 14. Lesion reduction from Lmax was calculated at 6 and 12 months during follow‐up. Results The 42 patients in this long‐term study had a median of nine baseline lesions and a median Lmax of 22 lesions. At 6 and 12 months of follow‐up, the median absolute reduction in AK lesions from Lmax with imiquimod 3.75% was 21 and 19, respectively. The median percentage reduction in lesions from Lmax to 6 and 12 months was 100% and 97.2%, respectively. Conclusions The ability of imiquimod 3.75% to eliminate clinical and subclinical lesions across an entire sun‐exposed field translates into sustained long‐term efficacy. Imiquimod 3.75% may therefore represent a first‐choice treatment for patients with AK.